2020
DOI: 10.3390/ijms21051638
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione–Allylsulfur Conjugates as Mesenchymal Stem Cells Stimulating Agents for Potential Applications in Tissue Repair

Abstract: The endogenous gasotransmitter H2S plays an important role in the central nervous, respiratory and cardiovascular systems. Accordingly, slow-releasing H2S donors are powerful tools for basic studies and innovative pharmaco-therapeutic agents for cardiovascular and neurodegenerative diseases. Nonetheless, the effects of H2S-releasing agents on the growth of stem cells have not been fully investigated. H2S preconditioning can enhance mesenchymal stem cell survival after post-ischaemic myocardial implantation; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 96 publications
1
13
0
Order By: Relevance
“…These data demonstrate that functionalized proteins which are a part of the hybrid hydrogel scaffold design can provide cell protection from the PhP damage acting as scavengers to free radicals. Having validated the TST assay to quantify oxidative damage associated with PhP, we next sought to measure the protective effects of a glutathione-conjugated garlic extract, named GSGa, which was able to provide a slow-release of H 2 S [ 30 , 49 ]. GSGa was added to the TST solution with PEGDA, and the solution was exposed to UV for 5 min.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These data demonstrate that functionalized proteins which are a part of the hybrid hydrogel scaffold design can provide cell protection from the PhP damage acting as scavengers to free radicals. Having validated the TST assay to quantify oxidative damage associated with PhP, we next sought to measure the protective effects of a glutathione-conjugated garlic extract, named GSGa, which was able to provide a slow-release of H 2 S [ 30 , 49 ]. GSGa was added to the TST solution with PEGDA, and the solution was exposed to UV for 5 min.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that GSGa treatment of cardiac cMSC improves their viability, proliferation, and migration rate without affecting their plasticity [ 49 ]. Our group also demonstrated that GSGa treatment for three days protects cMSC from induced oxidative stress (by H 2 O 2 and CoCl 2 administration), promoting the expression of Antioxidant Responsive Element (ARE) controlled enzymes ( Figure 3 A), such as NAD(P)H dehydrogenase (quinone 1 reductase) (NQO1), and pro-survival and proliferation, inducing proteins such as Bcl-2 and pERK1/2 [ 49 ]. Therefore, we sought to take advantage of these protective effects by preconditioning cMSC with a GSGa treatment prior to their encapsulation in photo-polymerizating hydrogels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations